إشكالية المصطلحات اللغوية العربية بين القدماء والمحدثين - محمدي، نوال (جامعة زيان عاشور الجلفة, 2023)
يحدد المصطلح مسار القراءة باختلاف منهجها، وهو في حد ذاته مفتاح العلوم وأدواتها الرئيسية، وقد أدرك المهتمون بالمصطلح أهمية المصطلحات وقيمتها لكل من العلوم، لأهميته البالغة واهتم به العلماء قديما وحديثا وتناولوه بالتعريف والدراسة، إلى درجة تسميته بعلم المصطلح Terminology، لدوره الفعال في حياة الخاصة والعامة من الناس واعتباره وسيلة لتعريف المفهوم ويقوم بشرح وتوضيح معناه بشكل دقيق وصحيح، ويستخدم لتوضيح المعاني. فبدون معرفة المصطلحات لا يمكننا إدراك العلم ولا فهم مكوناته الماضية في الاتساع والعمق. والتعريب هو تحويل كلمة من لغة أجنبية إلى اللغة العربية دون أن تفقد معناها ضمن سياق الجملة أو النص. والإشكال الذي طرح عند العلماء والمحدثين هو فيما إذا كانا علم اللغة وفقه اللغة متساويان ومترادفان في معرفة المعاني والكلمات أو في صناعة وجمع الألفاظ؟ The term defines the course of reading according to its different approaches, and it is in itself the key to science and its main tools. Those interested in the term have realized the sensibility of terminology and its value for each of the sciences, its extreme importance ,and scholars , ancient and modern, took care of it by definition and study, to the point of people and considering it as a means of for its effective role in the private and public lives of people and considering it as means of defining the concept and explaining and clarifying its meaning accurately and correctly, and is used to clarify meanings , without knowing the terms, we cannot perceive science nor understand its past components in breadth and depts. Arabization is the conversion of a word from a foreign language into Arabic without losing its meaning within the context of the sentence or text. The problem that has been put forward by scholars and modernists is whether linguistics and philology are equivalent and synonymous in knowing the meaning of words or in making, and collecting words.
Keywords: اللغة العربية -- المصطلحات اللغوية -- علم اللغة -- فقه اللغة